Sustainable End Milling of Difficult-Materials - Ginting, Yogie Rinaldy (Curtin University, 2017)
This research investigates Minimum Quantity Lubrication (MQL) and Cryogenic Liquid Nitrogen as alternatives to using traditional flood cooling for end milling difficult-materials to minimise the environmental burden of coolant. Three materials: Titanium Alloy (Ti-6A1-4V), Inconel 718 and Aluminium Metal Matrix Composites (AMMC) were investigated and the results were analysed using the Taguchi S/N ratio and the Pareto ANOVA. MQL was found to be the most feasible cooling alternative for the replacement of traditional flood cooling.